Academic resilience: Exploring the role of religiosity and self-efficacy in facing academic challenges - Muhammad Amin; Laili Syarifah; Fikri Hakim Ash Shiddiqy; Roma Wijaya (At Turots: Jurnal Pendidikan Islam, 2025)
Students inevitably face various academic challenges throughout their university journey. These challenges highlight the crucial role of academic resilience, which enables students to effectively channel their motivation, cognitive abilities, and actions towards achieving their academic goals. This research investigates how religiosity and self-efficacy positively contribute to students' academic resilience. Using a quantitative explanatory approach, data was collected from 196 students at STAI Syubbanul Wathon Magelang via questionnaires and analyzed using multiple linear regression. The findings indicate that religiosity significantly impacts academic resilience (p<0.001), as evidenced by a significance value of 0.000 (below 0.05). Similarly, self-efficacy also significantly influences academic resilience (p<0.001), with a significance value of 0.000 (below 0.05). Collectively, both religiosity and self-efficacy are confirmed to jointly enhance students' academic resilience.